2018
DOI: 10.21451/1984-3143-ar2018-0027
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms regulating follicle selection in ruminants: lessons learned from multiple ovulation models

Abstract: Selection of a single dominant follicle from a cohort of growing follicles is a unique biological process, a key step in female reproductive function in monovular species, and lies at the core of reproductive technologies in cattle. Follicle growth and the number of follicles that ovulate are regulated by precise endocrine, paracrine, and autocrine mechanisms. Most of our current understanding about follicle selection focuses on the role of FSH, LH, and the IGF family in follicle growth and selection of the do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 153 publications
0
16
0
Order By: Relevance
“…Numerous studies have attempted to understand the molecular, cellular, paracrine, hormonal, and follicular dynamics that produce selection of a single dominant follicle from the cohort of follicles that are growing during a follicular wave (Fortune et al 1991, Ginther et al 1996, Crowe 1999, Ireland et al 2000, Mihm et al 2002, Webb et al 20022016, Scaramuzzi et al 2011, Ginther 2016, Garcia-Guerra et al 2018) and yet all the mechanisms involved in this process have not been defined. This study focused on the role of circulating LH during the follicle selection mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have attempted to understand the molecular, cellular, paracrine, hormonal, and follicular dynamics that produce selection of a single dominant follicle from the cohort of follicles that are growing during a follicular wave (Fortune et al 1991, Ginther et al 1996, Crowe 1999, Ireland et al 2000, Mihm et al 2002, Webb et al 20022016, Scaramuzzi et al 2011, Ginther 2016, Garcia-Guerra et al 2018) and yet all the mechanisms involved in this process have not been defined. This study focused on the role of circulating LH during the follicle selection mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The use of precise characterization of follicular wave dynamics during ablation of LH pulses using acute treatment with a potent GnRH antagonist, Acyline, and subsequent replacement of LH action using a specific LHr agonist, hCG, allowed substantial insight into the hormonal control of follicle selection. The bovine model is particularly informative because of the extensive previous characterization of follicle dynamics and the complexities during follicle selection under different physiological conditions (Adams & Pierson 1995, Ginther et al 1996, 2016, Garcia-Guerra et al 2018, Gomez-Leon et al 2019.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TGF-β is significantly associated with ovulation rate, litter size, and prolificacy and thus plays a critical role in the folliculogenesis of small ruminants. Many studies reported that the mutations in TGF-β pathway-related genes enhanced ovulation rate (35-100%) in heterozygous animals [89]. Moreover, even if causative mutations for fecundity are not fully discovered, two other genetic variants were identified as FecX2W [90] and FecD [91], which are segregated in prolific sheep breeds in recent studies.…”
Section: Studies On Ovulation Rate In Small Ruminants As a Model Organismmentioning
confidence: 99%
“…In addition, understanding of the concept of ovarian follicular waves and hierarchical follicle development has also added to our understanding of the dynamics of follicle development and its role in the control of reproductive cycles. However, these topics are outside of the scope of this review and so, for further information on them, readers are directed to McNatty et al (2010), Bartlewski et al (2011), Forde et al (2011 and García-Guerra et al (2018c). Although prolificacy is a lowly heritable trait (h 2 ¼ 0.1-0.2; Van Vleck et al 1991;Á rnason and Jónmundsson 2008;Borg et al 2009), and determined mainly by polygenic processes, numerous major mutations play critical roles.…”
Section: Genetic Determination Of Ovarian Functionmentioning
confidence: 99%